THE OPTIMIZATION OF ACCOMMODATION OF THE SPRAYNOZZLE ON THE PIPELINE OF THE RAINGUN OF CONTINIOUS FRONTAL ACTION - V.A. CHERNOVOLOV; L.V. KRAVCHENKO (Advanced Engineering Research)
The reduction of power consumption of watering by the raingun with using of the lowpressured spraynozzles was investigated. The optimum distance between the spraynozzles on the pipeline under the various pressure meanings, the diameter of the outlet of the spraynozzle and the height of its installation were reckoned on the basis of the mathematical models and experimental data about the functions of distribution of precipitations on an angle of the watering zone and on its radiuses f ( α ) and f ( ρ). Two ways of accommodation of the spraynozzles on the pipeline are offered on condition of observation of the given watering zone on all the length of the pipeline and the work of the raingun pump at the maximal efficiency.